Cost Analysis of Biomass Briquette Stove - Thuchayapong, Nat; Tharawadee, Nattawut (Food Agricultural Sciences and Technology, 2019)
The purpose of this research was to study the value investment of using biomass briquette stove instead of LPG cooking stove. From the previous study (Thuchayapong and Inthagun, 2015), the saw dust biomass briquette were produced and tested its physical properties. The biomass briquette stove was constructed and tested its thermal effi ciency. In this research, the biomass briquette was improved its properties by changing binder from waste paper to cassava fl our. It was found that the physical properties of moisture content, density and shatter index of sawdust briquette had been improved. In addition, the cost analysis of biomass briquette stove had been evaluated by comparison with the gas stove in the household. It was found that, the production cost of biomass briquette stove was 578 Baht and that of biomass briquette was between 1.63 to 2.33 Baht/kg. Net Present Value (NPV), Internal Rate of Return (IRR) and Payback Period (PP) were evaluated in this research. It was found that the biomass briquette stove was worth the investment.